PERCEPTION OF HEALTHCARE PROVIDERS ABOUT SEXUALLY TRANSMITTED INFECTIONS - Viqar, Asma; Izhar, Viqar Izhar; Viqar, Muhammad Amaar (Pakistan Journal of Physiology, 2015)
Sexually transmitted infections represent a global health problem leading to social stigma and early morbidity and mortality. Prior to this study, different health care providers were dealing with sexually transmitted infections with various parameters and were not following the standard regime given by the WHO. The aim of this study was to investigate the perception of health care providers about sexually transmitted infections and its treatment guidelines. Methods: Cross-sectional questionnaire based study was conducted from health care providers(specialists, family physicians, homeopaths and others )of Lahore from Jan 2014 to December 2014. Data was collected with consent through convenience purposive sampling of randomly selected 100 specialists, 200 family physicians, 100 homeopaths and 100 others. Trained investigators pre-tested the validity and reliability of the questionnaire before use. Data of response was coded, entered and analyzed using SPSS. Results: Out of 500 practitioners 475 (95%) completed the questionnaire. Those excluded were due to insufficient data in questionnaire. Almost all respondents were aware of STIs and the guidelines and claimed to have decent knowledge. Apart from some disagreement on the user- friendliness and communication facilitating properties, the healthcare provider’s attitude were positive. Conclusion: Overall, all the healthcare providers knew about sexually transmitted infections. It was the treatment according to the guidelines, in which they differed. Specialists and Family physician in Lahore, Pakistan knew and followed the STIs guidelines while managing the patients.